1972
DOI: 10.1021/ja00762a051
|View full text |Cite
|
Sign up to set email alerts
|

Catalysis in organosilicon chemistry. III. Catalytic mode, solvent isotope effets, and transition-state structure in hydride expulsion from silicon

Abstract: shift is the highest so far known for a neutral organic suggests a similar explanation for nitrogen resonance as compound. The general correspondence with the well. Whether this is correct or not, the I5N shifts cyclopropane carbon shift, which has been interpreted in correspond to the substantial diamagnetic shieldings terms of ring current induced diamagnetic hi el ding,^" observed for the 3C resonances of aziridine.Abstract : Triphenylsilane, tribenzylsilane, and tributylsilane are methanolyzed to hydrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1972
1972
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…116 Reversible reaction between silanes and alcohols been studied and shown to increase the hydridic character of the silane through the formation of pentavalent species (Figure 179). 438 Very recently, this intermediate was observed by NMR at −70 °C, revealing an associative exchange mechanism. 439 In summary, obtaining direct experimental evidence for the formation of metal hydrides in the catalyzed alkene hydrofunctionalization methods has been a long sought challenge.…”
Section: Chemical Reviewsmentioning
confidence: 91%
See 3 more Smart Citations
“…116 Reversible reaction between silanes and alcohols been studied and shown to increase the hydridic character of the silane through the formation of pentavalent species (Figure 179). 438 Very recently, this intermediate was observed by NMR at −70 °C, revealing an associative exchange mechanism. 439 In summary, obtaining direct experimental evidence for the formation of metal hydrides in the catalyzed alkene hydrofunctionalization methods has been a long sought challenge.…”
Section: Chemical Reviewsmentioning
confidence: 91%
“…The team had speculated that the alcohol was necessary to increase the hydritic character of the silane via a pentavalent intermediate but these results suggested that they functioned as important silane ligands, 438,439 presumably as a result of increased Si elecrophilicity and more rapid ligand exchange with the catalyst. This novel reductant (Ph( i -PrO)SiH 2 ) improved the yields and rates of different metal-catalyzed radical hydrofunctionalizations 38,116,264,20 and allowed catalyst loadings and temperatures to be lowered.…”
Section: Mechanistic Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…If the reaction betbeen C6H5CH2Cs and H 2 did proceed then the mobile equilibrium according t o [6] ~o u l d restore the concentration of C6H5CH2Cs, uhile there is also the possibility of a reaction between CsI\JHC6Hi1 and H2. Either or both of these circilmstances could lead to n o Can.…”
Section: Resultsmentioning
confidence: 99%